Screening of elite eggplant (Solanum melongena) genotypes for bacterial wilt (Ralstonia solanacearum) in field conditions and their genetic association by using SSR markers - KHAPTE, P S; SINGH, T H; REDDY, D C LAKSHMANA (The Indian Journal of Agricultural Sciences, 2018)
Bacterial wilt (Ralstonia solanacearum) of eggplant (Solanum melongena L.) has been a major production constraint in the tropics and sub tropics of the world. Lack of understanding about host, pathogen and environment perhaps one of the reasons for limited success in controlling this disease. In present investigation, six elite genotypes of eggplant were screened against bacterial wilt in field conditions and later SSR screening was done to identify markers linked for resistant and susceptible lines, and their genetic clustering. At field level, the genotypes like CARI-1, IIHR-7 and IIHR-500A had shown resistant to bacterial wilt and recorded good yield. Further, 245 SSRs markers used for screening had shown good amplification, however only 37 primers were polymorphic, and microsatellite allele sizes were determined at their 74 loci. The average polymorphic information content was 0.315 and it ranged from 0.239 to 0.375. The SSR emh21J12 shown 170 bp band for the resistant genotypes and 160 bp band for the susceptible ones. Another SSR emf01K16 gave the unique banding pattern in resistant genotypes at 250 bp and susceptible at 260 bp. Dendrogram analysis classified these six genotypes into three main clusters. Cluster I consists of IIHR-575, IIHR-108 and IIHR-500A, where IIHR-500S was solitary. The cluster II consists Rampur local and IIHR-7 whereas, cluster III was solitary comprising CARI-1. It was revealed that the co-dominant markers such as SSR proved to be high effective tool in discriminating between resistant and susceptible genotypes, and classifying these genotypes based on genetic diversity. Hence, the field and molecular markers screening reveals that eggplant genotypes IIHR-7, IIHR-500A and CARI-1 are resistant to bacterial wilt and these resistant genotypes can be used for further breeding programme, and the identified SSR markers can be useful tool for marker assisted selection for bacterial wilt in eggplant.